The Cauchy Problem for a Special System of Quasilinear Equations (Journal of Partial Differential Equations, 1991)
We have obtained in this paper the existence of weak solutions to the Cauchy problem for a special system of quasillnear equations with physical interest of the form {\frac{&#8706}{&#8706t}(u + qz) + \frac{&#8706}{&#8706x}f(u) = 0 \frac{&#8706z}{&#8706t} + k&#966(u)z = 0 for the assumed smooth function &#966(u) by employing the viscosity method and the theory of compensated compactness.
Keywords: Entropy pair; weak solution